Physical activity of students at Junior High School 2 Weru Cirebon Regency for one week - Rifaldi, Mohamad Syaiful; Widyastuti, Suciati Rahayu (Universitas Tanjungpura, 2024)
This study aims to describe the physical activity of students of SMP Negeri 2 Weru Cirebon Regency for one week. The background of this research departs from the low level of physical activity among adolescents who spend more time with digital devices than physical activity. The research method uses a quantitative descriptive approach with survey techniques. The research sample was 186 students who were randomly selected from a population of 816 students. The data collection instrument used the Physical Activity Questionnaire for Adolescents (PAQ-A). The results showed that most of the students were at a moderate level of physical activity (36.55%). As many as 63.4% of students do not do sports activities in their free time. Regular physical activity is still low with a frequency of 2-3 times a week (49.5%). These findings show that awareness of the importance of physical activity has not been optimal among SMPN 2 Weru students. In conclusion, strategic interventions from schools, teachers, and parents are needed to promote a culture of healthy physical activity among adolescents.